Selecting Negotiation Techniques - Kozina, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The objective of the paper is to characterise negation techniques and to suggest the solution to the problem of selecting them within the negotiations planning process, either from a theoretical perspective or for particular negotiations situations. Although the techniques considered are used in the negotiation conducting phase within the process of their planning it is recommended that they be initially considered as specific tools to be applied in particular negotiations. The second part of the paper interprets and classifies negotiation techniques, based on relevant assumptions, in particular typological criteria. The selection of such techniques in negotiations planning is characterised and a case study on investment negotiations between two construction companies is presented. After describing the parties to and the scope and objectives of those negotiations, one party’s strategy was discussed along with the arguments and negotiation techniques that enabled them to implement their strategy. The final section of the paper looks at the directions for future research on negotiation techniques.